On the effect of labour durations using an anisotropic visco-hyperelastic-damage approach to simulate vaginal deliveries. (December 2018) - Vila Pouca, M.C.P.; Ferreira, J.P.S.; Oliveira, D.A.; Parente, M.P.L.; Mascarenhas, Teresa; Natal Jorge, R.M.
Abstract: Injuries sustained by the pelvic floor muscles during childbirth are one of the major risk factors for the development of pelvic floor dysfunctions. The ability to predict the loss of the tissue integrity and the most affected regions prior to the childbirth would represent a compelling difference in choosing the appropriate management of labour. Previous biomechanical studies, using the finite element method, were able to simulate a vaginal delivery and analyse the mechanical effects on the pelvic floor muscles during the passage of the foetus. Complementing these studies, the aim of this work is to improve the characterization of the pelvic floor muscles, by using an anisotropic visco-hyperelastic constitutive model, including a continuum mechanics damage model. Viscoelasticity is a key feature to obtain more realistic results since biological tissues present relaxation effects that allow larger deformations without damage. This work analyses the reaction forces and the loss of tissue integrity sustained by the pelvic floor and evaluates the effects of different durations of labour. A delaying pushing technique of rest and descend is also studied in this work. The results obtained showed that the reaction forces vary with the duration of labour, with higher force levels associated with higher stretch rates. The pubovisceral muscle is the most affected of the levator ani, presenting an affected region of approximately 30%. The relaxation properties of the tissue contribute to diminish the damage levels, supporting the theory of delayed pushing applied in the second stage of labour. Graphical abstract: